The Efficiency Performance of Global Islamic Banks - Norlina, Kadri; Rossazana, Ab-Rahim; Dyg Siti Zahrah, Abg. Abdillah (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This paper examines the efficiency performance of the Islamic banks that consist of 14 countries namely Bahrain, Bangladesh, Iran, Jordan, Kuwait, Lebanon, Malaysia, Pakistan, Qatar, Saudi, Tunisia, Turkey, UAE, and Yemen during the period of 2004-2011 with 44 Islamic banks involved. The efficiency estimates of individual banks are evaluated using the Data Envelopment Analysis (DEA) approach. The empirical findings suggest that during the period of study, pure technical efficiency outweighs scale efficiency in the global Islamic banking sector implying that the Islamic banks have been managerially efficient in exploiting their resources to the fullest extent. The empirical findings seem to suggest that the global Islamic banks have exhibited high pure technical efficiency. During the period of study it is found that pure technical efficiency has greater influence in determining the total technical inefficiency of the Global Islamic banking sectors.